THE EFFECT OF ISLAMIC BRAND ON CUSTOMER LOYALTY IN RETAIL BUSINESS - Nandy Alamsyah; Fajar Surya Ari Anggara (University of Darussalam Gontor, 2022)
Retail outlets that carry the halal concept will experience positive growth. This can be seen from the increase in retail outlets that carry the halal concept as Islamic brand. Retail companies that carry the halal concept target Indonesian people not only Muslim but also non-Muslim. Ismart Ponorogo is one of the mini markets that uses Islamic brand in sales and services. Upon that consideration, this research aims to analyze the role of Islamic influence in brand loyalty and customer loyalty also by quantitative approach for 67 respondents as customer in Ismart Ponorogo Retail Business. The results of this study indicate that Islamic brand has a positive effect on customer loyalty. In addition, implications of this study and directions for future research are also discussed.